Nadiem Makarim Planning Teacher Marketplace on CNN Indonesia News 2023: Analysis of Illocutionary Act - Listyarini; Ananta, Benny Dele Bintang (EDUJ : English Education Journal, 2024)
The procurement of a teacher marketplace, which is scheduled to commence in 2024, is the topic of discussion in this research. The implementation of a teacher marketplace plan has a significant influence on aspiring young instructors seeking teaching opportunities. The objective of this study is to classify the illocutionary acts in the news and to implementation of illocutionary acts in the news This study employs a descriptive qualitative approach, utilizing a systematic process for gathering literary sources, doing thorough readings of these sources, recording significant information, analyzing the data, and drawing conclusions. This study examines the concept of speech actions, specifically illocutionary acts, as they are manifested in the news articles found on the CNN Indonesia webpage. The researcher discovered that speakers employed 42.8% representational, 0% commissive, 28.6% expressive, 28.6% directive, and 0% declarative language in the news. Furthermore, the speech of the speakers in the news is categorized into five main types: representational, instructions, and expressive. Nevertheless, the problem of the marketplace teacher issue has significant adverse consequences for educators, as it might result in undesired joblessness within the educational sphere for both proponents and opponents of the issue.